2011
DOI: 10.1002/rcm.5215
|View full text |Cite
|
Sign up to set email alerts
|

A novel hydrogen migration of dialkylphosphonic acid esters using electrospray ionization tandem mass spectrometry

Abstract: In this paper, attention is focused on analysis of the fragmentation of α-hydroxy-β-amino phosphonate esters designed as inhibitors of protein kinase A. An interesting proton migration mechanism in the cleavage of the P-C bond is investigated by electrospray ionization tandem mass spectrometry. A possible rearrangement mechanism is proposed and verified by high-resolution mass spectra using isotope deuterium/hydrogen-exchange technology and additionally checked by detailed DFT calculation based on Gaussian sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It was found that the fragmentation pathways of P–C bonds were different from those of phosphates and phosphoramidates containing P–O and P–N bonds, respectively . Several interesting rearrangement reactions have been observed, such as hydrogen‐atom migration from the hydroxyl to the phosphoryl group for α‐hydroxyl dialkylphosphonic acid esters, neutral phosphoryl amine loss from phosphonate peptides, and oxygen‐atom migration to phosphoryl groups for [(4‐substituted‐benzoylamino)phenylmethyl]phosphonic acid diisopropyl esters . Furthermore, it was found that P–C bonds could be easily cleaved in the gas phase under our experimental conditions.…”
mentioning
confidence: 99%
“…It was found that the fragmentation pathways of P–C bonds were different from those of phosphates and phosphoramidates containing P–O and P–N bonds, respectively . Several interesting rearrangement reactions have been observed, such as hydrogen‐atom migration from the hydroxyl to the phosphoryl group for α‐hydroxyl dialkylphosphonic acid esters, neutral phosphoryl amine loss from phosphonate peptides, and oxygen‐atom migration to phosphoryl groups for [(4‐substituted‐benzoylamino)phenylmethyl]phosphonic acid diisopropyl esters . Furthermore, it was found that P–C bonds could be easily cleaved in the gas phase under our experimental conditions.…”
mentioning
confidence: 99%